2017
DOI: 10.1007/978-3-319-67744-6_29
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Design Decision Rationale with Decision Cards

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Spaces for capturing design decisions should have a low threshold for usage and should not enforce a particular structure in order to accommodate the different strategies of design teams. We proposed and trialed one such format, the Decision Cards, reported in [19]. These cards are lightweight formats that have been used in design workshops to capture artefacts and their rationale in a standardized way, but without influencing the process.…”
Section: Design Direction #3 -Dedicate Space For Design Decisionsmentioning
confidence: 99%
“…Spaces for capturing design decisions should have a low threshold for usage and should not enforce a particular structure in order to accommodate the different strategies of design teams. We proposed and trialed one such format, the Decision Cards, reported in [19]. These cards are lightweight formats that have been used in design workshops to capture artefacts and their rationale in a standardized way, but without influencing the process.…”
Section: Design Direction #3 -Dedicate Space For Design Decisionsmentioning
confidence: 99%
“…Whilst decisions made by the development team occur iteratively throughout the process and will result in evolutions of multiple artefacts, the ISO standard 9241-210 is very silent about how to record and process such design decisions. Empirical observation [14] [15] have shown that development teams often make extensive use of annotations. Annotations are flexible, they can assume many forms (such as text, sketching, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…and be attached to any type of artefacts, making them a suitable mechanism to provide complementary information throughout the development process. The study performed by Gutierrez et al [15] pointed out that annotations are used by members of development teams to: i) record the results of discussion including decisions and upcoming tasks, communicate and inform other team members of the work done, ii) gather internal and external feedback on artefacts stored in the workspace, iii) conduct usability evaluations by documenting information and by recording conversation between design teams and UX experts, and justify design choices, and document the design choices by describing them retrospectively. While previous work [15] argued for the use of annotations for user interface prototypes, this paper extends the use of annotations made over various artefacts (including prototypes) by providing a generic engineering solution to connect them across multiple artefacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation